Far from the coast: organohalogen bioaccumulation in spinner dolphins from the Southwestern Atlantic - Caroline A.C. Corrêa; Bárbara M.R. Manhães; Nara Oliveira-Ferreira; Elitieri B. Santos-Neto; Eduardo R. Secchi; Juliana C. Di Tullio; Rodrigo C. Genoves; Haydée A. Cunha; Tatiana L. Bisi; Alexandre F. Azevedo; José Lailson-Brito (Marine Pollution Bulletin, 2026)

Range-wide monitoring reveals demographic vulnerability in Lahille's bottlenose dolphins - Fábio G. Daura-Jorge; Paula Laporta; Ignacio B. Moreno; Paulo H. Ott; Paulo A.C. Flores; Pedro Volkmer de Castilho; André S. Barreto; Rodrigo Cezar Genoves; Carolina Bezamat; Alexandre M.S. Machado; Eduardo R. Secchi; Silvina Botta; et al. (Biological Conservation, 2026)

Grapevine adopts different strategies in response to drying regimes. Procrastinator or escaper? - C. Morabito; J. Orozco; A. Asteggiano; C. Medana; A. Schubert; M.A. Zwieniecki; F. Secchi (Journal of Plant Physiology, 2025)

Antarctic sea ice as a driver of humpback whale migration timing in the southeast Pacific - Renan C. de Lima; Fernando Félix; Ben Haase; Eduardo R. Secchi (Polar Biology, 2025)

At sea mortality estimates of loggerhead turtle (Caretta caretta) in Southwestern Atlantic Ocean - Ademir S. Maruyama; Paul G. Kinas; Eduardo R. Secchi; Jonatas H.F. Prado; Sérgio C. Estima; Andrine P. Silva; Fabrício S.C. Oliveira; Danielle S. Monteiro (Biological Conservation, 2024)

Niche partitioning among odontocetes in a marine biogeographic transition zone of the western South Atlantic Ocean - Ana Carolina Tatsch; Renan C. de Lima; Eduardo R. Secchi; Silvina Botta (Marine Biology, 2024)

Feeding habits of South American and sub‐Antarctic fur seals during their nonbreeding season in the southwestern Atlantic Ocean - Renan C. de Lima; Thaise L. de Albernaz; Eduardo R. Secchi; Julieta D. Cebuhar; Silvina Botta (Marine Mammal Science, 2024)
Stomach contents of South American ( Arctocephalus australis ) ( n = 219) (SAFS) and sub‐Antarctic ( A. tropicalis ) ( n = 37) (SFS) fur seals were opportunistically sampled from 1980 to 2021 to examine their feeding habits and resource partitioning in southern Brazil while in their nonreproductive periods. SAFSs mainly consumed abundant coastal pelagic species, such as Anchoa marinii and Doryteuthis sanpaulensis , resulting in high sexual trophic niche overlap. The frequency of occurrence (%FO) of fish prey, especially the overexploited Micropogonias furnieri , decreased between 1980–1992 and 2007–2021, while squid increased. For SFSs, offshore squids such as Ommastrephes bartramii and Illex argentinus were the most important prey considering both sexes in the long‐term. The interspecific trophic niche overlap was low, but it is likely underestimated since it increased with the inclusion of scat samples from SFSs. This sample‐size effect was also observed in Shannon's diversity index, which was lower for underrepresented SFSs. Marine debris ingestion was detected in both species (SAFS %FO = 2.7; SFS %FO = 8.3), with only flexible plastic material found. This study brings novel information on feeding habits of fur seal species in the extreme south of Brazil, as well as unprecedented information about their ecology during the nonreproductive period.

The deep dive of organohalogen compounds: Bioaccumulation in the top predators of mesopelagic trophic webs, pygmy and dwarf sperm whales, from the Southwestern Atlantic ocean - Nara de Oliveira-Ferreira; Elitieri B. Santos-Neto; Bárbara M.R. Manhães; Vitor L. Carvalho; Letícia Gonçalves; Pedro V. de Castilho; Eduardo R. Secchi; Silvina Botta; Milton C.C. Marcondes; Adriana C. Colosio; Marta J. Cremer; Haydée A. Cunha; et al. (Chemosphere, 2023)

Ecological traits of the franciscana dolphin ( Pontoporia blainvillei ) from the Late Pleistocene to the present days based on stable isotope analysis - Thayara S. Carrasco; Renan C. de Lima; Gabriel S. da Mota; Silvina Botta; Eduardo R. Secchi; Ana Maria Ribeiro; Jorge Ferigolo; Francisco S. Buchmann (Marine Mammal Science, 2023)
Late Pleistocene fossils from southern Brazil provide a unique opportunity to study the diet and habitat use of the extant franciscana dolphin ( Pontoporia blainvillei ) prior to human influence. Here, we subject 19 fossil and 21 contemporary specimens to stable carbon and oxygen isotope analysis (after first ruling out diagenesis via Fourier transform infrared spectroscopy). The two groups differ in their isotopic composition (PERMANOVA, p 13 C values and recent samples more disparate δ 18 O values. Their isotopic niches show an overlap of ~20%, with that of the fossils being slightly wider (SEAc = 2.25‰ 2 versus 1.84‰ 2 ). We attribute these differences to impoverished modern fish communities and temporal changes in freshwater influx.

Physical-biological drivers modulating phytoplankton seasonal succession along the Northern Antarctic Peninsula - Raul Rodrigo Costa; Afonso Ferreira; Márcio S. de Souza; Virginia M. Tavano; Rodrigo Kerr; Eduardo R. Secchi; Vanda Brotas; Tiago S. Dotto; Ana C. Brito; Carlos Rafael B. Mendes (Environmental Research, 2023)

Potential biases in dietary interpretation derived from stable isotope analysis of small dolphin teeth - Genyffer C. Troina; Clarissa R. Teixeira; Frank Dehairs; Eduardo R. Secchi; Silvina Botta (Marine Environmental Research, 2023)

Assessing bias in aerial surveys for cetaceans: Results from experiments conducted with the franciscana dolphin - Federico Sucunza; Daniel Danilewicz; Artur Andriolo; Franciele R. de Castro; Marta Cremer; Pablo Denuncio; Emanuel Ferreira; Paulo A. C. Flores; Paulo H. Ott; Martin S. Perez; Dan Pretto; Camila M. Sartori; et al. (Frontiers in Marine Science, 2022)
Line transect aerial surveys are widely used for estimating abundance of biological populations, including threatened species. However, estimates obtained with data collected from aircraft are often underestimated because of visibility bias and bias in estimating group sizes from a fast-moving platform. An assessment of multiple sources of bias in aerial surveys were carried out in Brazilian coastal waters by experiments on multiple survey platforms (i.e., boat, airplane and helicopter). These studies focused on evaluating visibility bias (perception and availability bias) and potential differences in the estimation of group sizes from different types of platforms used in franciscana ( Pontoporia blainvillei ) abundance surveys. The ultimate goal was to develop correction factors to improve accuracy of estimates of density and population size for this threatened dolphin. Estimates of density and group sizes computed from boats were assumed to be unbiased and were compared to estimates of these quantities obtained from an airplane in the same area and period. In addition, helicopter surveys were conducted in two areas where water turbidity differed (clear vs. murky waters) to determine surfacing-diving intervals of franciscana groups and to estimate availability for aerial platforms. Abundance computed from the aerial survey data underestimated the true abundance by about 4-5 times, with ~70% of the total bias resulting from visibility bias (~80% from availability bias and ~20% from perception bias) and ~30% from bias in estimates of group size. The use of multiple survey platforms in contrasting habitats provided the opportunity to compute correction factors that can be used to refine range wide abundance estimates of the threatened franciscana given certain assumptions are met. Visibility bias and group size bias were substantial and clearly indicate the importance for accounting for such correction factors to produce unequivocal population assessment based on aerial survey data.

Phylogeography of the Endangered Franciscana Dolphin: Timing and Geological Setting of the Evolution of Populations - Luana Nara; Marta J. Cremer; Ana P. C. Farro; Adriana Castaldo Colosio; Lupércio A. Barbosa; Carolina P. Bertozzi; Eduardo R. Secchi; Bruna Pagliani; Paula Costa-Urrutia; Maria C. Gariboldi; Cristiano Lazoski; Haydée A. Cunha (Journal of Mammalian Evolution, 2022)

Segregation of diets by sex and individual in South American fur seals - Renan C. de Lima; Valentina Franco-Trecu; Thayara S. Carrasco; Pablo Inchausti; Eduardo R. Secchi; Silvina Botta (Aquatic Ecology, 2022)

Integrating morphology and DNA barcoding to assess cetacean diversity in Brazil - Vanessa S. Silva; Natália Skueresky; Fernando Lopes; Tabata K. Koch; Paulo Henrique Ott; Salvatore Siciliano; André S. Barreto; Eduardo R. Secchi; Ana Carolina O. de Meirelles; Vitor Luz Carvalho; João C. G. Borges; Daniel Danilewicz; et al. (Mammal Research, 2021)

Changes in Phytoplankton Communities Along the Northern Antarctic Peninsula: Causes, Impacts and Research Priorities - Afonso Ferreira; Raul R. Costa; Tiago S. Dotto; Rodrigo Kerr; Virginia M. Tavano; Ana C. Brito; Vanda Brotas; Eduardo R. Secchi; Carlos R. B. Mendes (Frontiers in Marine Science, 2020)

Temporal and individual variation in the diet of the Neotropical otter, Lontra longicaudis (Olfers, 1818) (Carnivora, Mustelidae), as revealed by stable isotope analysis of vibrissae - Thayara S. Carrasco; Renan C. de Lima; Silvina Botta; Rodrigo Machado; Paulo C. Simões-Lopes; Paulo H. Ott; Eduardo R. Secchi (Mammalian Biology, 2020)

Geographic-Scale Harvest Program to Promote Invasivorism of Bigheaded Carps - Wesley W. Bouska; David C. Glover; Jesse T. Trushenski; Silvia Secchi; James E. Garvey; Ruairi MacNamara; David P. Coulter; Alison A. Coulter; Kevin Irons; Andrew Wieland (Fishes, 2020)
Invasive bigheaded carps, genus Hypophthalmichthys, are spreading throughout the Mississippi River basin. To explore the efficacy of a consumer-based market (i.e., invasivorism) to manage them, we developed a conceptual model and evaluated three harvest approaches—direct contracted removal, volume-based incentives (“fisher-side” control), and set-quota harvest (“market-side” control). We quantified the efficacy of these approaches and potential population impact in the Illinois River. Contracted removal was effective for suppressing small populations at the edge of the range but cannot support a market. “Fisher-side” removals totaled 225,372 kg in one year. However, participation was low, perhaps due to reporting requirements for fishers. The “market-side”, set-quota approach removed >1.3 million kg of bigheaded carp in less than 6 months. Larger, older fish were disproportionately harvested, which may hinder the ability to suppress population growth. Total density declined in one river reach, and harvest may reduce upstream movement toward the invasion fronts. With sufficient market demand, harvest may control bigheaded carp. However, lack of processing infrastructure and supply chain bottlenecks could constrain harvest, particularly at low commodity prices. Given the geographical scale of this invasion and complicated harvest logistics, concerns about economic dependence on invasivorism that encourage stock enhancement are likely unmerited.

Diverse groups of fungi are associated with plastics in the surface waters of the Western South Atlantic and the Antarctic Peninsula - Ana L. d. F. Lacerda; Maíra C. Proietti; Eduardo R. Secchi; Joe D. Taylor (Molecular Ecology, 2020)
Marine plastic pollution has a range of negative impacts for biota and the colonization of plastics in the marine environment by microorganisms may have significant ecological impacts. However, data on epiplastic organisms, particularly fungi, is still lacking for many ocean regions. To evaluate plastic associated fungi and their geographic distribution, we characterised plastics sampled from surface waters of the western South Atlantic (WSA) and Antarctic Peninsula (AP), using DNA metabarcoding of three molecular markers (ITS2, 18S rRNA V4 and V9 regions). Numerous taxa from eight fungal phyla and a total of 64 orders were detected, including groups that had not yet been described associated with plastics. There was a varied phylogenetic assemblage of predominantly known saprotrophic taxa within the Ascomycota and Basidiomycota. We found a range of marine cosmopolitan genera present on plastics in both locations, i.e., Aspergillus, Cladosporium , Wallemia and a number of taxa unique to each region, as well as a high variation of taxa such as Chytridiomycota and Aphelidomycota between locations. Within these basal fungal groups we identified a number of phylogenetically novel taxa. This is the first description of fungi from the Plastisphere within the Southern Hemisphere, and highlights the need to further investigate the potential impacts of plastic associated fungi on other organisms and marine ecosystems.

Cetacean distribution in relation to environmental parameters between Drake Passage and northern Antarctic Peninsula - Manuela Bassoi; Jorge Acevedo; Eduardo R. Secchi; Anelio Aguayo-Lobo; Luciano Dalla Rosa; Daniel Torres; Marcos C. O. Santos; Alexandre F. Azevedo (Polar Biology, 2020)

Origin and foraging ecology of male loggerhead sea turtles from southern Brazil revealed by genetic and stable isotope analysis - Luciana Medeiros; Danielle S. Monteiro; Silvina Botta; Maíra C. Proietti; Eduardo R. Secchi (Marine Biology, 2019)

Isotopic niche of the Neotropical otter, Lontra longicaudis (Carnivora, Mustelidae), in different coastal aquatic systems in southern Brazil - Thayara S. Carrasco; Silvina Botta; Rodrigo Machado; Paulo C. Simões-Lopes; Oldemar Carvalho-Junior; Paulo H. Ott; Elton P. Colares; Eduardo R. Secchi (Hydrobiologia, 2019)

Individual foraging specialization and sexual niche segregation in South American fur seals - Renan C. de Lima; Valentina Franco-Trecu; Damián G. Vales; Pablo Inchausti; Eduardo R. Secchi; Silvina Botta (Marine Biology, 2019)

Taxonomy, phylogeny and ecology of cultivable fungi present in seawater gradients across the Northern Antarctica Peninsula - Vívian N. Gonçalves; Gislaine A. Vitoreli; Graciéle C. A. de Menezes; Carlos R. B. Mendes; Eduardo R. Secchi; Carlos A. Rosa; Luiz H. Rosa (Extremophiles, 2017)

Long-term spatial and temporal patterns of sea turtle strandings in southern Brazil - Danielle S. Monteiro; Sérgio C. Estima; Tiago B. R. Gandra; Andrine P. Silva; Leandro Bugoni; Yonat Swimmer; Jeffrey A. Seminoff; Eduardo R. Secchi (Marine Biology, 2016)

Remarkably low genetic diversity and strong population structure in common bottlenose dolphins (Tursiops truncatus) from coastal waters of the Southwestern Atlantic Ocean - Pedro F. Fruet; Eduardo R. Secchi; Fábio Daura-Jorge; Els Vermeulen; Paulo A. C. Flores; Paulo César Simões-Lopes; Rodrigo Cézar Genoves; Paula Laporta; Juliana C. Di Tullio; Thales Renato O. Freitas; Luciano Dalla Rosa; Victor Hugo Valiati; et al. (Conservation Genetics, 2014)

Mitochondrial DNA diversity of the Southwestern Atlantic humpback whale (Megaptera novaeangliae) breeding area off Brazil, and the potential connections to Antarctic feeding areas - Márcia H. Engel; Nelson J. R. Fagundes; Howard C. Rosenbaum; Matthew S. Leslie; Paulo H. Ott; Renata Schmitt; Eduardo Secchi; Luciano Dalla Rosa; Sandro Luis Bonatto (Conservation Genetics, 2008)

Growth hormone secretion in relation to plasma lactate and glucose concentrations during a maximal treadmill exercise test in horses - V. Borromeo; F. Ferrucci; E. Zucca; A. Berrini; C. Secchi (Veterinary Research Communications, 2008)

Effects of growth hormone on oocyte in vitro maturation and its localization in the canine cumulus-oocyte complexes - S. Chigioni; C. Secchi; V. Borromeo; S. Modina; M. S. Beretta; G. C. Luvoni (Veterinary Research Communications, 2008)

Identification of Four Tuna Species by Means of Real-Time PCR and Melting Curve Analysis - A. Dalmasso; E. Fontanella; P. Piatti; T. Civera; C. Secchi; M.T. Bottero (Veterinary Research Communications, 2007)

Heterophile Antibodies in Horse Plasma Interfering in an Enzyme-linked Immunosorbent Assay - V. Borromeo; A. Berrini; D. Gaggioli; C. Secchi (Veterinary Research Communications, 2007)

The Effect of Species-Specific FSH Administration During In vitro Maturation of Bovine Oocytes on Embryonic Developmental Capability - V. Borromeo; S. Bramani; S. Modina; V. Lodde; A. M. Luciano; C. Secchi (Veterinary Research Communications, 2006)

Monoclonal Antibody Capture Fluorometric Enzyme-Linked Immunosorbent Assay for Detection of Equine Growth Hormone in Plasma - V. Borromeo; F. Abbate; A. Berrini; A. Bartolone; C. Secchi (Veterinary Research Communications, 2005)